Confusing identity, overlapping demands, and conflict in leadership: A deep probe into the problem of Rajbanshi-led movements in North Bengal - Basistha, Nandini (2016)
Recent upsurge of Kamtapur Liberation Organisation (KLO) activism in the Northern part of West Bengal makes a severe blow in the security of that region. For fighting with the situation, both Central Government and State Government give stress on 'Development-Security Nexus'. Different region-specific schemes and extension of benefits under the policy of protective discrimination for communities has initiated to soothe the economic grievances of the non-Bengali communities. On the other hand, excessive raids, arrests and ban over political activities has been limited the scope for politics of separatism. But Rajbanshi-led KLO insurgency, is a fallout of continuous failure of their non-violent movements in democratic arena. Rajbanshis are demanding separate territory from 1947. But, due to some inherent problems of Rajbanshi-led movements - like fragmented ethno-linguistic identity, overlapping territorial demands and conflict between leadership - they never united on a single platform. So grievances of common Rajbanshis got marginalised in the majoritarian democratic politics. This ultimately provoked Rajbanshi youths to insurgency. In this article, the author tries to discuss three major problems of Rajbanshi-led democratic movements - viz. confusion over ethnic origin and linguistic status of Rajbanshis, overlapping territorial demands of statehood, and conflict between leaders. The article ends up with the information of cross-border activism of KLO and their mode of operation. - Reproduced.
Keywords: Leadership; Social movements